Negotiating independence, choice and autonomy : experiences of parents who coordinate personal assistance on behalf of their adult son or daughter - Brennan, Ciara; Traustadóttir, Rannveig; Rice, James; Anderberg, Peter (Disability & Society, 2016)
Article 19 of the UN Convention on the Rights of Persons with Disabilities requires states to provide personal assistance services. This article is based on qualitative research in Iceland, Norway and Sweden, carried out between 2012 and 2013. The overall study focused broadly on the implementation of Article 19. This article, however, reports findings based on a particular group of participants within the larger study: non-disabled parents who coordinate personal assistance schemes for their adult son or daughter. The article examines the various ways in which the parents, the majority of whom were mothers, negotiate principles of independence, choice and autonomy for their adult son or daughter who requires intensive support, including assistance with communicating. The aim is to explore, in the context of the Convention and the principles of the independent living movement, how to acknowledge and conceptualise personal assistance schemes that require another person to manage on behalf of the user. © 2016 Informa UK Limited, trading as Taylor & Francis Group